Persepsi Siswa terhadap Kinerja Guru Pendidikan Jasmani Olahraga dan Kesehatan di SMA Yadika Baturaja - Dedi Sapta Wijaya; Dessy Wardiah; Daryono Daryono (Departement of Mathematics Education, 2023)
The purpose of this study was to examine students' perceptions of the performance of physical education, sports and health teachers at SMA Yadika Baturaja. The research method used in this research is a quantitative descriptive method. The population of this research is SMA Yadika Baturaja. Data collection techniques carried out with research questionnaires. Research data analysis technique with proportion analysis. The results of the study can be concluded that students' perceptions of the performance of PJOK teachers because of the pedagogical aspects owned by the teacher amounted to 78% or the good category, student perceptions of the performance of PJOK teachers because of the personality aspects owned by the teacher amounted to 69.9% or the category is quite good, student perceptions on the performance of PJOK teachers because of the social aspect that the teacher has is 82.37% or the good category, and students' perceptions of the performance of PJOK teachers because of the professional aspect of the teacher is 80.2% or the good category. While students' perceptions of PJOK teacher performance as a whole amounted to 76.61% in the good category.